Murder Ballads: Exhuming the Body Buried beneath Wordsworth's Lyrical Ballads. - Brennan, David John (punctum Books, 2016)
In 1798, William Wordsworth and Samuel Taylor Coleridge were engaged in a top secret experiment. This was not, as many assume, the creation of a book of poetry. A book emerged, to be sure--the landmark Lyrical Ballads. But in Murder Ballads, David John Brennan posits that the two poets were in fact pursuing far different ends: to birth from their poems a singular, idealized Poet. Despite their success, such Frankensteinian pursuits proved rife with consequence for the men. Doubts and questions plagued them: What does it mean to be a poet if your work is not your own? Who is best fit to lay claim to a parcel of poetic property that was collaboratively crafted and bequeathed to a fictitious Poet? How does one kill a Poet born of one's own hand? Blending critical examination with jocular playlets-in-verse featuring the authors of the two books in baffled conversation, Murder Ballads reopens a 200-year-old cold case that never received a proper investigation: Who was the first true Author of Lyrical Ballads, and how exactly did he die?